Interaction of cyanine dyes with nucleic acids. 2. Spectroscopic properties of methyleneoxy analogues of Thiazole Orange - Yarmoluk, S.M.; Kovalska, V.B.; Smirnova, T.V.; Shandura, M.P.; Kovtun, Y.P.; Matsuka, G.K. (Биополимеры и клетка, 1996)
A series of asymmetric cyanine dyes based on methylenoxy benzothiazole terminal hetero-cycle was synthesized. Absorption and fluorescent properties of these dyes and their complexes with nucleic acids were investigated. The best results were obtained with 2-[(3-methyl-2(3H)-benzothiazolyliden)-methyl]-5,6-dioxymethylene-3-methylbenzothiaz olium p-toluenesulfonate (Cyan 13). A possible model of binding monomethyne benz-thiazole cyanine dyes with double-stranded nucleic acids is proposed. Синтезовано серію асиметричних монометинових ціанінових барвників з метиленоксибензтіазоловим термінальним гетероциклом. Досліджено їх абсорбційні та флюоресцентні властивості, спектральні властивості їх комплексів з нуклеїновими кислотами. Найкращі результати одержані з n - толулол сул ьфо на том 2-[ ( 3 - метил-2 ( ЗН )-бензотіазоліліден) метил] -5,6-диоксиметилен-3-метил-бензотіазолію. Пропонується гіпотетична модель взаємодії монометинових бензтіазолових барвників з двоспіральними нуклеїновими кислотами. Синтезирована серия асимметричных монометиновых цианиновых красителей с метиле ноксибензтиазоловым терминальным гетероциклом. Исследованы их абсорбционные и флюоресцентные свойства, спектральные свойства их комплексов с нуклеиновыми кислотами. Наилучшие результаты получены с n-толулолсульфонатом 2-[( 3-метил-2( ЗН )-бензотиазолилиден)метил]-5,6-диоксиметилен-З-метилбензотиазолия. Предлагается гипотетическая модель взаимодействия монометиновых бензтиазоловых красителей с двуспиральными нуклеиновыми кислотами.